Vision Systems for the Location of Citrus-Fruit in a Tree Canopy - Moltó, Enrique; Pla, F.; Juste, Florentino (2017)
One of the main factors for the automation of citrus harvesting to be made economically viable is to achieve an acceptably efficient vision system. For this purpose, algorithms capable of identifying and locating the greatest amount of fruits must be designed, which minimize the rate of misclassified objects.